A Study On The Scope Of Innovative Business Model For The Growth Of Start Up In India (Journal of Pharmaceutical Negative Results, 2023)
India's innovative business model for startup growth is fairly broad and has a lot of promise, according to the report's findings. There are several factors to consider when writing a business plan for the growth of startups in India. The report has information on the market, the client, the technology, the team, the business model, the funding, and the ecosystem. It is an effort to have qualitative research and focus on the ideas where start ups will get success.